3 2 x + 1 ⋅ 4 x − 1 = 3 6
Find x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
3 2 x + 1 ⋅ 4 x − 1 = 3 6 3 2 x ⋅ 3 ⋅ 4 4 x = 3 6 9 x ⋅ 4 x = 3 3 6 × 4 3 6 x = 4 8 x = lo g 3 6 4 8
Next level genius.
3^(2x+1) *4^(x-1)=3^(2x+1) *2^2(x-1)=6^2x *3/4=36 apply log with base 6 and use properties of logarithm to get value for x.
Problem Loading...
Note Loading...
Set Loading...
3 2 x + 1 ⋅ 4 x − 1 lo g 3 6 ( 3 2 x + 1 ⋅ 4 x − 1 ) ( 2 x + 1 ) lo g 3 6 3 + ( x − 1 ) lo g 3 6 4 2 x lo g 3 6 3 + x lo g 3 6 4 + lo g 3 6 3 − lo g 3 6 4 x ( lo g 3 6 3 2 + lo g 3 6 4 ) x ( lo g 3 6 3 6 ) x = 3 6 = lo g 3 6 3 6 = lo g 3 6 3 6 = lo g 3 6 3 6 = lo g 3 6 3 6 − lo g 3 6 3 + lo g 3 6 4 = lo g 3 6 ( 3 3 6 ⋅ 4 ) = lo g 3 6 4 8